Three to get deadly - Evanovich, Janet (New York : St. Martin's Paperbacks, 1998)
In Three to Get Deadly, a "saintly" old candy store owner is on the lam---and bounty hunter extraordinaire Stephanie Plum is on the case. As the body count rises, Stephanie finds herself dealing with dead drug dealers and slippery fugitives on the chase of her life. And with the help of eccentric friends and family, Steph must see to it that this case doesn't end up being her last. . . .
Reprint. Previously published in hardcover: New York : Scribners, 1997.
83484
Keywords: Plum, Stephanie (Fictitious character) -- Fiction; Bail bond agents -- New Jersey -- Fiction; Fugitives from justice -- Fiction; Trenton (N.J.) -- Fiction; Mystery fiction